2015
DOI: 10.1080/10705422.2014.985412
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Involvement in Nonmetropolitan LGBTQ Organizations: A Multimethod Qualitative Exploration

Abstract: Organizations serving lesbian, gay, bisexual, transgender, and queer (LGBTQ) communities provide services aimed at improving the health and well-being of LGBTQ people, yet may face limited resources and community support in nonmetropolitan communities. This study seeks to understand LGBTQ individuals' motivations for becoming and staying involved in nonmetropolitan LGBTQ organizations. Data collection methods included interviews, participant observation, and focus groups. Six categories of motivations emerged:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Our study was cross-sectional, so it is not certain whether those who volunteered for LGBTI organisations were already more closely connected to these communities or whether volunteering for LGBTI organisations provides a greater sense of connectedness that they would not have otherwise had. While no previous research has made this comparison for older lesbian and gay people, studies involving American lesbian and gay volunteers of all ages found participants were motivated to volunteer with such organisations out of a desire for social connectedness to the associated communities (Gates et al, 2016; Paceley et al, 2015). Studies could be conducted in future that explore the social and community networks of older lesbian women and gay men, and how volunteering within LGBTI communities, plays a part in connectedness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was cross-sectional, so it is not certain whether those who volunteered for LGBTI organisations were already more closely connected to these communities or whether volunteering for LGBTI organisations provides a greater sense of connectedness that they would not have otherwise had. While no previous research has made this comparison for older lesbian and gay people, studies involving American lesbian and gay volunteers of all ages found participants were motivated to volunteer with such organisations out of a desire for social connectedness to the associated communities (Gates et al, 2016; Paceley et al, 2015). Studies could be conducted in future that explore the social and community networks of older lesbian women and gay men, and how volunteering within LGBTI communities, plays a part in connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, non-LGBTI organisations refer to those that are not specifically focused on LGBTI populations, such as charities that work with older people more generally. On the whole, LGBTI organisations are perhaps more likely to ensure culturally safe environments and supportive networks and might also give opportunities for older people to connect with younger lesbian and gay people (Gates et al, 2016; Paceley et al, 2015). At least in some cases, the potential benefits to well-being of volunteering in non-LGBTI organisations may be countered if older lesbian or gay volunteers have concerns about experiencing stigma or discrimination within the organisations.…”
Section: Introductionmentioning
confidence: 99%
“…Queer and trans adults were more likely to be involved in an LGBTQ community center or nonprofit organization if they felt attached to their residential communities, felt attached to the queer and trans community, or had been victimized by a stranger based on their sexual orientation or gender identity. A qualitative study examined the motivations to LGBTQ community center involvement in a small town (Paceley, Keene, & Lough, 2015). They found that queer and trans individuals were motivated to be involved in the local queer and trans community to access support, establish a local LGBTQ community, to give back to their community, to affirm their own queer or trans identity, to support an LGBTQ organization, and/or to be involved in a way that connected their professional and private lives.…”
Section: Queer and Trans Activism And Young Adultsmentioning
confidence: 99%
“…Social workers engaging with LGBTQ+ people can benefit from understanding the impact and intersection of volunteerism, health, mental health, as well as systems of care, reduction in isolation and stigma, connection to peers and community, and well-being of all sexual and gender minority populations (Ding, Ehrenfeld, Edmiston, Eckstrand, & Beach, 2020;Frost & Meyer, 2012;Ramirez-Valles, Fergus, Reisen, Poppen, & Zea, 2005). Few studies have explicitly examined LGB volunteers' experiences and those that have often used convenience sampling or other unreliable approaches (Gates et al, 2016;Kayal, 1993;Molina, Dirkes, & Ramirez-Valles, 2017;Paceley, Keene, & Lough, 2015;Ramirez-Valles et al, 2014). Lack of representativeness related to the sample is a common challenge of exploring LGBTQ+ issues in social work, volunteerism, and mental health, all of which can have a detrimental impact upon the accuracy and applicability of research findings.…”
Section: Volunteerism and Lgbtq+ Mental Healthmentioning
confidence: 99%